Twenty-four-hour ambulatory blood pressure variability is associated with total magnetic resonance imaging burden of cerebral small-vessel disease - Yang, Shuna (Clin Interv Aging, 2018)
BACKGROUND: Lacunae, brain atrophy, white matter hyperintensity, enlarged perivascular space and microbleed are magnetic resonance imaging (MRI) markers of cerebral small-vessel disease (cSVD). Studies have reported that higher blood pressure variability (BPV) predicted cardiovascular risk in hypertensive patients; however, the association between BPV and the total MRI burden of cSVD has not been investigated. In this study, we aimed to explore this relationship between BPV and cSVD MRI burden. METHODS: We prospectively recruited patients who attended our hospital for annual physical examination. Twenty-four-hour ambulatory BP monitoring was performed using an automated system. BPV was quantified by SD, weighted SD, and coefficient of variation. One point was awarded for the presence of each marker, producing a score between 0 and 5. Spearman correlation and ordinal logistic regression analyses were used to test the relationship between BPV and total cSVD MRI burden. RESULTS: A total of 251 subjects with an average age of 68 years were enrolled in this study, and 52.6% were male; 163 (64.94%) had one or more markers of cSVD. Correlation analysis indicated that higher systolic BP (SBP) levels and BPV metrics of SBP were positively related to higher cSVD burden. Ordinal logistic regression analyses demonstrated that higher SBP levels and SBP variability were independent risk factors for cSVD. There were no significant differences in 24-hour, day and night diastolic BP levels or BPV metrics of diastolic BP among the five subgroups. CONCLUSION: Twenty-four-hour, day and night SBP levels and SBP variability were positively related to cSVD burden. Higher SBP levels and SBP variability were independent risk factors for cSVD.